Genus Osmanthus Lour. (Oleaceae) and Osmanthus suavis King ex C. B. Clarke new record for the flora of Vietnam - Quang, Bui Hong (Academia Journal of Biology, 2016)
The genus Omanthus Lour. had about 35 species in the world including 5 sections, distributed in tropical and subtropical in South East Asia, America. The genus Osmanthus Lour. was published by Loureiro (1790) with the typus was O. fragrans Lour. In Vietnam, based on Loureiro (1790), F. Gagnepain (1933), P. H. Ho (2003), T. D. Ly (2003) and B. H. Quang (2014) there are 2 species in sections Leiolea, Osmanthus. During studying specimens of this section in the Herbaria, we introduced O. suavis. in section Siphosmanthus, as a new record for flora of Vietnam. This species has distribution in Lao Cai, Thanh Hoa. Species O.suavis. was closed to O. delavayi by Cymes fascicled in leaf axils or terminal, but O. suavis different with O. delavayi, by (leaves petiole 5-7 (10) mm, primary viens 5-8 on each side of midrib and Drupe blue-black, ellipsoid or ovoid, ca. 8 x 5 mm.). vs (leaves petiole 2-3 mm, primary viens 4-5 on each side of midrib, Drupe blue-black, ellipsoid or ovoid, ca. 1-1.5 cm). In this article, we introduce nomenclature, key to species, morphology and illustration, distribution and research specimen of all species in genus Osmanthus Lour. in Vietnam.